2017
DOI: 10.23846/tw2202unc
|View full text |Cite
|
Sign up to set email alerts
|

Promoting partner and couples HIV testing using self-test kits in Kenya

Abstract: The International Initiative for Impact Evaluation (3ie) is an international grant-making non-governmental organization promoting evidence-informed development policies and programs. We are the global leader in funding, producing and synthesizing high-quality evidence of what works, for whom, why and at what cost. We believe that high-quality and policy-relevant evidence will help make development more effective and improve people's lives. 3ie impact evaluations3ie-supported impact evaluations assess the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This high proportion underscores the promise of HST to increase testing rates, and corroborates other studies showing high acceptability of HST and high uptake of this testing method, 13,14 including among male partners of pregnant women. 29 In the parent RCT of these analyses, men in the intervention arm had much higher uptake of testing in general compared with the 2 control arms (79.4% vs. 37% and 28%, respectively), and in the intervention arm, 95% of the men who tested for HIV used the HST kit. 23 The Joint United Nations Programme on HIV/AIDS (UNAIDS) put forth a target that states by 2020, 90% of people living with HIV should know their status, 90% of people with diagnosed HIV should receive antiretroviral therapy, and 90% of people on antiretroviral therapy should be virally suppressed.…”
Section: Discussionmentioning
confidence: 96%
“…This high proportion underscores the promise of HST to increase testing rates, and corroborates other studies showing high acceptability of HST and high uptake of this testing method, 13,14 including among male partners of pregnant women. 29 In the parent RCT of these analyses, men in the intervention arm had much higher uptake of testing in general compared with the 2 control arms (79.4% vs. 37% and 28%, respectively), and in the intervention arm, 95% of the men who tested for HIV used the HST kit. 23 The Joint United Nations Programme on HIV/AIDS (UNAIDS) put forth a target that states by 2020, 90% of people living with HIV should know their status, 90% of people with diagnosed HIV should receive antiretroviral therapy, and 90% of people on antiretroviral therapy should be virally suppressed.…”
Section: Discussionmentioning
confidence: 96%
“…One intervention for TB-HIV co-infection found that community-based TB screening increased screening efforts but decreased presumed TB and TB positive cases identified. 45 There were a total of 39 community service interventions focused on HIV testing -17 interventions distributed HIVST to men (primary or secondary distribution), [46][47][48][49][50][51][52][53][54][55][56][57][58] 15 provided community/workforce testing (non-HIVST), 52,53,55,[59][60][61][62][63][64][65][66][67][68][69][70][71] and 11 provided home-based HIV testing services. 46,54,61,69,[72][73][74][75] Community services outperformed standard of care facility services 48,52,60,61,65,67,72,73 and mobile and targeted venue testing such as work were more cost...…”
Section: Community Servicesmentioning
confidence: 99%
“…63,64,68 Primary distribution of HIVST increased reach testing. 48,52,53,55 Secondary HIVST distribution increased testing among men when given to female partners living with HIV as part of index testing, 47,58 ANC clients, [49][50][51]57 young women, 56 and when HIVST was left for male adults and adolescents who were not home during door-to-door distribution. 48,54 Only one community service intervention examined the impact on linkage for men.…”
Section: Community Servicesmentioning
confidence: 99%